Pemberdayaan Kelompok Sadar Wisata Taman Mangrove dalam Upaya Perbanyakan Rambai (Sonneratia caseolaris) - Yunita, Rizmi; Rahman, Abdur; Dharmaji, Deddy; Rezeki, Amalia; Indrayatie, Eko Rini (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
The Tourism Awareness Group (Pokdarwis) of the sustainable Mangrove Apple Park is one of the groups formed by the Barito Kuala Regency Government of South Kalimantan as actors in tourism development related to empowering coastal communities who care about the mangrove flora and fauna environment. The purpose of community service activities for partner groups is to utilize mangrove vines as material for propagation/nursery, selecting good media for sowing. The solution offered is to provide information on knowledge about the mangrove apple plant, select planting media and conduct training and demonstrations in order to increase the knowledge and skills of partner groups. The method of delivering material is through meetings and discussions. The training is in the form of demonstrations and demonstrations as well as evaluating the activities that have been carried out. The results of service activities for partner groups have provided a change in attitude and knowledge of partner groups from not knowing enough to knowing enough about propagation/breeding, choosing good media for sowing. Meetings with partner groups have an impact on increasing the variety of knowledge and abilities, where members of partner groups in propagation/breeding efforts, the selection of good media for sowing as an increase in partner group knowledge tends to lead to the same level or evenly.